2016
DOI: 10.1001/jamaneurol.2016.2742
|View full text |Cite
|
Sign up to set email alerts
|

Aberrations in Peripheral Inflammatory Cytokine Levels in Parkinson Disease

Abstract: IMPORTANCEThe association of nonmotor features and Parkinson disease (PD) is increasingly recognized. Evidence suggests that inflammation may play a role in PD pathologic features and symptoms.OBJECTIVE To quantitatively summarize the peripheral inflammatory cytokine data available for patients with PD.DATA SOURCE A systematic search of peer-reviewed English-language articles from PubMed, PsycINFO, and the Cochrane Library without year limitation was performed from December 7, 2015, to March 23, 2016. The sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
343
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 435 publications
(369 citation statements)
references
References 76 publications
20
343
4
2
Order By: Relevance
“…Different PET studies could confirm an increased microglial activation in the midbrain of PD patients that was correlated to disease progression (Ouchi et al, 2005; Gerhard et al, 2006; Koshimori et al, 2015). This goes in line with a study reporting that the pro-inflammatory cytokines TNFα, IL-6 and IL-1β were elevated in the cerebrospinal fluid (CSF) of PD patients (Qin et al, 2016). So far, all evidence on hand points towards an increased microglial activation with a pro-inflammatory “M1” phenotype that might contribute to PD progression.…”
Section: Microglial Activity In Pdsupporting
confidence: 89%
“…Different PET studies could confirm an increased microglial activation in the midbrain of PD patients that was correlated to disease progression (Ouchi et al, 2005; Gerhard et al, 2006; Koshimori et al, 2015). This goes in line with a study reporting that the pro-inflammatory cytokines TNFα, IL-6 and IL-1β were elevated in the cerebrospinal fluid (CSF) of PD patients (Qin et al, 2016). So far, all evidence on hand points towards an increased microglial activation with a pro-inflammatory “M1” phenotype that might contribute to PD progression.…”
Section: Microglial Activity In Pdsupporting
confidence: 89%
“…Studies reporting increased serum RANTES levels in association with IL-15, IL-8, and MCP-1 in PD patients suggest that the dysregulation in the peripheral cytokine network might be related to the pathogenesis and underlying neurodegeneration [19, 27, 28]. In addition, RANTES serum levels were reported to correlate with disease severity [29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with MSA were found to have an increase in proinflammatory TNFα in serum [6]. Other evidence shows increased peripheral inflammatory cytokines, including IL-6, TNFα, and IL-1β in the serum of patients with PD [7]. Epidemiologic evidence also indicated that increased serum levels of IL-6 were associated with a greater risk of PD development [8], though the results of subsequent studies were variable regarding significant increases or associations of IL-6 with symptoms [912].…”
Section: Introductionmentioning
confidence: 99%